2019
DOI: 10.1111/apce.12259
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of microcredit default in Indian self‐help groups

Abstract: This exploratory study was conducted to examine the reasons behind credit defaults in Self‐help Group‐based microfinance programs in India. The study adopted the mixed‐method approach. Focus group discussions (FGDs) were conducted to collect information, and thematic analysis was followed to analyze data to identify the possible causes of loan defaults in self‐help groups (SHGs). Further, 120 defaulting and 120 performing SHGs were selected through stratified random sampling method. Finally, 960 respondents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Previous studies have pointed out that micro‐financed SHGs are not efficient in generating sources for entrepreneurial activities (Dhake & Narkhede, 2019) and may lead to credit defaults in SHGs (Panda & Reddy, 2020). Nonetheless, studies have also established that membership in SHGs leads to the economic well‐being of the household (Hoffman et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have pointed out that micro‐financed SHGs are not efficient in generating sources for entrepreneurial activities (Dhake & Narkhede, 2019) and may lead to credit defaults in SHGs (Panda & Reddy, 2020). Nonetheless, studies have also established that membership in SHGs leads to the economic well‐being of the household (Hoffman et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To capture this difference, we have included the migrant status of the spouse of the household head. The number of household members is negatively related to defaults at SHGs (Panda & Reddy, 2020). Caste is a key variable that captures the social capital dimension and is related to the accessibility of a member to SHGs (Hoffman et al., 2021).…”
Section: Empirical Model and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirmed that t a single factor could not emerge. Furthermore, a four-factor Positive Stimulus (5 items) (Panda, 2009;Ledgerwood, 1999) (Panda and Reddy, 2019;Panda, 2009Panda, , 2016 (10-point scale 1 5 strongly disagree and 10 5 strongly agree) 0.96 2.1 Intermediary Accountability (Panda and Reddy, 2019;Panda, 2009Panda, , 2016 The intermediary agency does not take ownership of the operations of micro-enterprise and success of micro-enterprise…”
Section: Common Methods Biasmentioning
confidence: 99%
“…The second major barrier for the SHG members to undertake micro-enterprises are the "intermediation assumptions" which impact negatively to the motivation for microentrepreneurship (Panda and Reddy, 2019;Panda, 2009). A typical intermediary, a nongovernment organization (NGO), and each NGO deals with a large number of SHGs in the provision of intermediation services with donor and grant support.…”
Section: H1 the Intermediation Benefits Positively Impact The Shg Mem...mentioning
confidence: 99%